Asymmetric synthesis of homochiral Baylis-Hillman products employing (R)-N-methyl-N-alpha-methylbenzyl amide - Davies, S; Smethurst, C; Smith, A; Smyth, G (2000)
The conjugate addition of (R)-N-methyl-N-α-methylbenzyl amide to tert-butyl cinnamate followed by an asymmetric aldol reaction and subsequent N-oxidation/Cope elimination affords β-substituted homochiral Baylis-Hillman products in good yield. Copyright (C) 2000 Elsevier Science Ltd.